Merdeka Belajar: Solusi Awal Transformasi Pendidikan Indonesia? - Vira Rizki Amalia; Masduki Asbari (Journal of Information Systems and Management (JISMA), 2023)
The purpose of this study is to find out the independent learning method that can be implemented in schools and to find out the assessment system in the Merdeka Belajar program as a school graduation requirement. This study report uses a descriptive qualitative method by taking notes because the source of the data was obtained by listening to an oral narrative from the CNN Indonesia Youtube channel entitled "Nadiem Makarim's Solution to Overcoming Indonesia's Education Problems" presented by the Minister of Education and Culture Nadiem Anwar Makarim . The results of this study explain that the Merdeka Belajar program is one of the first steps to start transforming Indonesian education with a process of creativity and innovation in each school, because in the world today and in the future, uniformity is not something that can improve the quality of education in Indonesia, therefore it is necessary to create new breakthroughs that can make education in Indonesia creative, innovative and collaborative.